Improving Speaking Skills Through Communicative Language Teaching (CLT): A Literature Review - Gregian Carl Judilla; Reyna Mae Morre; Marven cayanong; Joemar Miñoza; M. Saleh Yahya Himni (Saniya Institute, 2025)
Communicative Language Teaching (CLT) is an approach that prioritizes meaningful interaction and student engagement to enhance language proficiency particularly in speaking. In today’s globalized world, where communication is key, CLT proves valuable for English as a Second Language (ESL) learners who often struggle with limited vocabulary, low confidence, and insufficient speaking practice. This literature review, analyzing 30 studies from 2017 to 2025, affirms CLT’s effectiveness in boosting fluency, accuracy, vocabulary, and confidence through interactive activities such as role-plays and discussions. It also fosters creativity, autonomy, and enjoyment in learning. Despite these benefits, challenges like overcrowded classrooms, limited resources, insufficient teacher training, and student anxiety can hinder CLT’s success. To address these, the study recommends enhanced teacher training, resource-rich and supportive environments, confidence-building activities, and integrating CLT into broader educational policies, including MTB-MLE in the Philippines. In conclusion, CLT is not just a technique, it’s a transformative approach that empowers learners to use language with confidence and real-world purpose.